Edukasi Lingkungan : Pelatihan Pembuatan Plasbut Paving Block Menggunakan Tekonologi Ramah Lingkungan di SMPN 4 Panarukan Satap Melalui Program MES - Ani Listriyana; Nurul Amalia Silviyanti; Vidya Pratiwi (Universitas 45 Surabaya, 2025)
This community service program was carried out at SMPN 4 Panarukan Satap, Situbondo Regency, with the aim of providing environmental education and skills in processing plastic waste into plasbut paving blocks using environmentally friendly technology. The background of this activity is the low level of community awareness around the school in maintaining environmental cleanliness, as well as the habit of drying rengginang (traditional crackers) on piles of garbage. On the other hand, the school has an extracurricular program focusing on environmental awareness, but it faces obstacles in the waste processing activities, particularly due to air pollution caused by the smoke released during the production of paving blocks made from plastic, sand, and coconut fiber (plasbut paving blocks). The implementation methods included socialization, training on paving block production utilizing solar energy and LPG, and mentoring through the Marine Entrepreneur School (MES) extracurricular program. The results showed an increase in students’ knowledge and skills, production efficiency up to 75% faster compared to manual methods, and a reduction in air pollution through the use of smoke-filtering technology. The sustainability of the program is supported by its integration into the school’s co-curricular activities. This program has implications for improving environmental awareness, enhancing students’ entrepreneurial skills, and reducing the volume of plastic waste in coastal areas.